2014
DOI: 10.1007/s10508-014-0289-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence to Suggest that Women’s Sexual Behavior is Influenced by Hip Width Rather than Waist-to-Hip Ratio

Abstract: Waist-to-hip ratio (WHR) is an important ornament display that signals women's health and fertility. Its significance derives from human development as a bipedal species. This required fundamental changes to hip morphology/musculature to accommodate the demands of both reproduction and locomotion. The result has been an obstetric dilemma whereby women's hips are only just wide enough to allow the passage of an infant. Childbirth therefore poses a significant hip width related threat to maternal mortality/risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Studies on cheating behavior provide further evidence that PA can come with relational costs. Hughes and Gallup () found that women with low waist‐to‐hip ratios (WHR)—a paradigmatic feature of female PA (Brooks, Jordan, Shelly, & Dixson, ; Singh, ; Singh, Dixson, Jessop, Morgan, & Dixson, ; Streeter & McBurney, ; but see also Simpson, Brewer, & Hendrie, )—reported having more extra‐relationship partners relative to women with high WHR. Similarly, men with lower levels of fluctuating asymmetry report having more extra‐relationship partners (Gangestad & Thornhill, ; Thornhill & Gangestad, ).…”
mentioning
confidence: 99%
“…Studies on cheating behavior provide further evidence that PA can come with relational costs. Hughes and Gallup () found that women with low waist‐to‐hip ratios (WHR)—a paradigmatic feature of female PA (Brooks, Jordan, Shelly, & Dixson, ; Singh, ; Singh, Dixson, Jessop, Morgan, & Dixson, ; Streeter & McBurney, ; but see also Simpson, Brewer, & Hendrie, )—reported having more extra‐relationship partners relative to women with high WHR. Similarly, men with lower levels of fluctuating asymmetry report having more extra‐relationship partners (Gangestad & Thornhill, ; Thornhill & Gangestad, ).…”
mentioning
confidence: 99%
“…Associations between female WHR and metrics of fertility led researchers to assess whether female WHR also associates with engagement in sexual behavior. Some work found correlations between female WHR and sexual behaviors (e.g., lower WHR was associated with greater sexual unrestrictedness; Hughes & Gallup, 2003); however, others have failed to find any associations (e.g., Simpson et al, 2014). Even if correlations exist, causal direction is unclear (e.g., body shape might predict sexual behavior or body shape might influence socialization, interaction dynamics, or others' behaviors).…”
Section: Waist-to-hip Ratiomentioning
confidence: 99%